The Role of the Autopsy During the COVID-19 Pandemic in a Case of Sudden Death with Fatal Hemorrhage and Thrombosis Post chAdox1nCoV-19 VACCINE - A Case Review - Daisley, Hubert; Daisley, Martina; Joseph, Haille; Daisley, Johann; Phagoo, Kavita (Brazilian Journal of Case Reports, 2025)
This case report describes an elderly patient who experienced sudden death from fulminant pulmonary, gastrointestinal and nasal hemorrhage one day after receiving his second dose of the AstraZeneca ChAdox1nCoV-19 vaccine, during the SARS-CoV-2 pandemic. The patient was PCR negative for SARS-CoV-2, but had thrombocytopenia, erythroblastosis and markedly elevated D-Dimer levels. The clinical diagnoses considered included hypovolemic shock, Vaccine-Induced Immune Thrombotic Thrombocytopenia (VITT), PCR negative SARS-CoV-2 infection, Vaccine-Associated Enhanced Disease (VAED), Vaccine-induced Covid-19 mimicry Syndrome and Adenovirus induced thrombocytopenia and thrombosis. The autopsy findings revealed diffuse pulmonary hemorrhage, thrombosis of the microvascular system of the lungs, myocardium and kidneys, together with metastatic foamy cell prostate carcinoma to the lung and bone marrow. Disseminated Intravascular coagulation (DIC) secondary to advanced prostate cancer remained a significant differential diagnosis. This case report highlights the complexity of diagnosing (VITT) and the importance of considering other potential causes of thrombocytopenia and thrombosis, including the presence of solid tumors, particularly in elderly patients. The autopsy provided crucial insights into the patient’s condition.